1992
DOI: 10.1002/1097-0142(19920915)70:6<1616::aid-cncr2820700630>3.0.co;2-7
|View full text |Cite
|
Sign up to set email alerts
|

Pain in ambulatory patients with lung or colon cancer. Prevalence, characteristics, and effect

Abstract: Background. Few studies have evaluated the epidemiology and effect of pain in ambulatory patients with cancer who are undergoing active therapy. This information is needed to develop strategies for supportive care in this population. Methods. The prevalence and characteristics of pain were determined in a prospective survey of ambulatory patients with lung or colon cancer. To reduce bias and acquire comprehensive information, the methodology used face‐to‐face interviews by trained quality assurance analysts, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
64
0
3

Year Published

1996
1996
2011
2011

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 154 publications
(71 citation statements)
references
References 19 publications
4
64
0
3
Order By: Relevance
“…The interference section assesses the effect of pain on general activity, mood, walking, work, relationships, sleep and enjoyment of life, using a 0-10 NRS, where 0 indicates no interference by pain and 10 indicates that pain completely interferes with the specific component. The BPI interference score (sum of individual interference question scores) gives a useful indicator of the effect of pain on physical, psychological and social function [22]. The BPI can be assessed using individual questions in isolation (e.g.…”
Section: Methodsmentioning
confidence: 99%
“…The interference section assesses the effect of pain on general activity, mood, walking, work, relationships, sleep and enjoyment of life, using a 0-10 NRS, where 0 indicates no interference by pain and 10 indicates that pain completely interferes with the specific component. The BPI interference score (sum of individual interference question scores) gives a useful indicator of the effect of pain on physical, psychological and social function [22]. The BPI can be assessed using individual questions in isolation (e.g.…”
Section: Methodsmentioning
confidence: 99%
“…Approximately one-third of patients have pain while undergoing active therapy for the disease, and more than three-quarters have pain during the last stages of illness [1,2]. Fortunately, experience suggests that cancer pain can be relieved in more than 70% of patients using a simple opioid-based regimen [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…Some authors stated that one third of the patients complain of pain in more than one location, while others report that up to 81% of the patients complain of pain in two or more locations [21][22][23] . In the first appointment, 82.5% of the patients complained of moderate to severe pain according to the verbal scale, which is very close to some studies that showed that more than 60% of the patients complain of pain of the same severity 21,24 .…”
Section: Discussionmentioning
confidence: 99%